Determination of mineral content in the ficus deltoidea leaves - Nihayah Mohammad,; Yong, Kar Wei; Nur Faizah Abu Bakar, (penerbit ukm, 2012)
Ficus deltoidea leaves were widely used as a tea beverages in Malaysia with no information of its mineral content. Hence the mineral content of two species of Ficus deltoidea leaves were investigated. The dried leaves of F. deltoidea var. angustifolia and F. deltoidea var. deltoidea were acid digested and mineral elements of Na, Mg, K, Ca, Mn, Cr, Fe and Zn were determined using ICP–MS. Magnesium, potassium, sodium, manganese, iron and zinc were found to be present in the leaves of F. deltoidea var. angustifolia and F. deltoidea var. deltoidea. Concentration of magnesium (1934 mg/L), manganese (58.37 mg/L), iron (6.89 mg/L) and zinc (1.77 mg/L) in F. deltoidea var. deltoidea species were significantly (P < 0.05) higher than in F. deltoidea var. angustifolia species with concentration of 317 mg/L, 29.62 mg/L, 4.55 mg/L and 1.26 mg/L for magnesium, manganese, iron and zinc respectively. Meanwhile, concentration of sodium in F. deltoidea var. deltoidea species (3.13 mg/L) was found to be significantly (P < 0.05) lower than the concentration in F. deltoidea var. angustifolia species (9.11 mg/L). The finding showed that the leaves of F. deltoidea var. deltoidea has higher nutritional value than the leaves of F. deltoidea var. angustifolia. Leaves of Ficus deltoidea especially the F. deltoidea var. deltoidea species contain high amount of magnesium, manganese and potassium. Therefore, tea made of this leaves can be served as a good source of minerals for human consumption.